Implementasi Steganografi Menggunakan Metode Spread Spectrum Dalam Pengamanan Data Teks Pada Citra Digital - Nasution, Yusuf Ramadhan; Furqan, Mhd.; Sinaga, Meri (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
Various techniques are used to protect digital information, especially information that is kept secret from people who are not entitled to the right of access to information, one of which is the technique of steganography. Steganography technique is a technique used to secure data by inserting or hiding data into an object without changing the shape of the object; one of the objects is a digital image. The steganography technique also has several methods, namely the Spread Spectrum method. Spread Spectrum is a method of communication where information signals are spread across all available frequencies by selecting where to insert data at low frequencies and adding pseudo-noise (PN). This study secures text data with the Spread Spectrum steganography technique on digital image objects by the steps of changing the value of the RGB pixel image and text data into binary, spreading the text data, followed by key generation and the modulation process of spreading text data with the generated key results. To produce a stegano image with an RGB pixel value that changes the value of 0 to 1 value that does not affect the color reproduction of the RGB pixel image.